Use of a critical phosphorus dilution curve to improve potato crop nutritional management - Zamuner, Ester Cristina (2016)
Plant diagnostic methods to determine P deficiencies need the definition of a critical concentration value which represents the minimum P concentration required to achieve maximum growth. The critical P concentration (Pc) has not been determined for potato. We designed a five years experiment with the objective of using the relationship between P concentrations and total dry matter (TB) yield to determine and validated the Pc, expressed as a function of TB. The Pc was described by the model: 3.919*TB -0.304 where total biomass (TB) ranged from 1 to 16 Mg ha−1. The P nutritional index (PNI), which is the ratio between the measured whole plant P concentration and Pc, was associated with the relative tuber yield measured at harvest. The results from this study support the use of PNI from 60 to 80 days after planting to determine potato crop P nutritional status.